Influenza vaccine: progress in a vaccine that elicits a broad immune response. (2nd September 2021) - Isakova-Sivak, Irina; Stepanova, Ekaterina; Mezhenskaya, Daria; Matyushenko, Victoria; Prokopenko, Polina; Sychev, Ivan; Wong, Pei-Fong; Rudenko, Larisa
ABSTRACT: Introduction: The licensed seasonal influenza vaccines predominantly induce neutralizing antibodies against immunodominant hypervariable epitopes of viral surface proteins, with limited protection against antigenically distant influenza viruses. Strategies have been developed to improve vaccines' performance in terms of broadly reactive and long-lasting immune response induction. Areas covered: We have summarized the advancements in the development of cross-protective influenza vaccines and discussed the challenges in evaluating them in preclinical and clinical trials. Here, the literature regarding the current stage of development of universal influenza vaccine candidates was reviewed Expert opinion: Although various strategies aim to redirect adaptive immune responses from variable immunodominant to immunosubdominant antigens, more conserved epitopes are being investigated. Approaches that improve antibody responses to conserved B cell epitopes have increased the protective efficacy of vaccines within a subtype or phylogenetic group of influenza viruses. Vaccines that elicit significant levels of T cells recognizing highly conserved viral epitopes possess a high cross-protective potential and may cover most circulating influenza viruses. However, the development of T cell-based universal influenza vaccines is challenging owing to the diversity of MHCs in the population, unpredictable degree of immunodominance, lack of adequate animal models, and difficulty in establishing T cell immunity in humans. ABBREVIATIONS: cHA: chimeric HA; HBc: hepatitis B virus core protein; HA: hemagglutinin; HLA: human leucocyte antigen; IIV: inactivated influenza vaccine; KLH: keyhole limpet hemocyanin; LAH: long alpha helix; LAIV: live attenuated influenza vaccine; M2e: extracellular domain of matrix 2 protein; MHC: major histocompatibility complex; mRNA: messenger ribonucleic acid; NA: neuraminidase; NS1: non-structural protein 1; qNIV: quadrivalent nanoparticle influenza vaccine; TRM : tissue-resident memory T cells; VE: vaccine effectiveness; VLP: virus-like particles; VSV: vesicular stomatitis virus